Histone acetylation-mediated regulation of the Hippo pathway. - Dipanjan Basu; Miguel Reyes-Múgica; Abdelhadi Rebbaa (PLoS ONE)
The Hippo pathway is a signaling cascade recently found to play a key role in tumorigenesis therefore understanding the mechanisms that regulate it should open new opportunities for cancer treatment. Available data indicate that this pathway is controlled by signals from cell-cell junctions however the potential role of nuclear regulation has not yet been described. Here we set out to verify this possibility and define putative mechanism(s) by which it might occur. By using a luciferase reporter of the Hippo pathway, we measured the effects of different nuclear targeting drugs and found that chromatin-modifying agents, and to a lesser extent certain DNA damaging drugs, strongly induced activity of the reporter. This effect was not mediated by upstream core components (i.e. Mst, Lats) of the Hippo pathway, but through enhanced levels of the Hippo transducer TAZ. Investigation of the underlying mechanism led to the finding that cancer cell exposure to histone deacetylase inhibitors induced secretion of growth factors and cytokines, which in turn activate Akt and inhibit the GSK3 beta associated protein degradation complex in drug-affected as well as in their neighboring cells. Consequently, expression of EMT genes, cell migration and resistance to therapy were induced. These processes were suppressed by using pyrvinium, a recently described small molecule activator of the GSK 3 beta associated degradation complex. Overall, these findings shed light on a previously unrecognized phenomenon by which certain anti-cancer agents may paradoxically promote tumor progression by facilitating stabilization of the Hippo transducer TAZ and inducing cancer cell migration and resistance to therapy. Pharmacological targeting of the GSK3 beta associated degradation complex may thus represent a unique approach to treat cancer.